Analisis Komoditas Unggulan Subsektor Peternakan di Kabupaten Barito Kuala - Ash'ari, Fuzi; Hasiani, Yarna; Samudera, Raga (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2022)
One way to develop superior agricultural products in the livestock sub-sector in the region is to identify the dominant sub-sector of livestock products in the region. This study aims to identify the leading livestock sector in Barito Kuala Regency. The process of collecting data was carried out using a survey method based on secondary data. Secondary data collection was sourced from documents and data from the livestock sub-sector owned by the Central Statistics Agency (BPS) of Barito Kuala Regency and South Kalimantan Province. The method used for data analysis is in the form of Location Qoutient (LQ) analysis to determine the base and non-base subsectors. The input data in the calculation is the number of livestock populations in a times series from 2017 to 2020. Based on the results of Location Qoutient (LQ) analysis, the LQ value of dairy cattle, horses, sheep and laying hens is 0, broilers with an LQ value of 0, 51 and ducks at 0.95 were categorized as non-basic commodities, while the largest LQ value was (1). Free-range chicken by 6.19 then (2). The Muscovy duck is 5.74, (3). Pig of 4.72, (4). Buffalo cattle of 4.13, (5). Beef cattle of 3.01, and (6). Goat by 1.30. The livestock commodities are categorized as basic commodities. The potential of livestock commodities can not only be developed for the needs of the area itself but can also be fulfilled in the surrounding area.